Dynamic deformation behaviour of 0.51C–1.72Si–0.83Mn–0.56Co high-strength steel. Issue 13 (2nd September 2021) - Zou, Minqiang; Huang, Chengcong; Qi, Liang; Guan, Renguo; Zhu, Fusheng
Abstract : In this paper, high-strength steel is prepared by different heat-treatment processes. Through split Hopkinson pressure bar experiment, optical microscope, scanning electron microscope and X-ray diffractometer, the microstructure evolution and mechanical behaviour under high strain rate were studied. The results show that the samples prepared by the two-step isothermal method have the highest compressive strength under the same strain rate, especially at 5000 s −1, the highest can reach 2097 MPa. The retained austenite undergoes transformation under high strain rate conditions, which improves the plastic deformation ability of the material. Compared with the one-step isothermal heat-treatment process, the two-step isothermal heat-treatment process can better control the strength and plasticity under high strain rate deformation conditions.